Honey, reducing sugar, diastase number, Kyrgyzstan - J. Iskakova; A. Deydiev; A. Kulmyrzaev (MANAS: Journal of Engineering)
Fermented foods are of great importance world-wide because they improve nutritional and organoleptic properties of the raw materials used, and they have prolonged shelf-life. Bozo is still produced and consumed with different recipes and methods in Central Asia, Turkey, South Russia, East European countries, African countries, Middle East, and Northern Iran. These beverages are valuable source of carbohydrates, vitamins, minerals, organic acids and other biologically active components. It can be marketed as a functional food product due to content of the number of different probiotic lactic acid bacteria. Lactic acid bacteria and yeasts responsible for Bozo fermentation were identified as Leuconostoc, Lactobacillus, Pediococcus, Weissella and Saccharomyces, Candida, Geotrichum, Pichia, Nadsonia, respectively. In this review, preparation methods, chemical composition and nutritional value as well as microflora composition of Bozo and similar cereal-based fermented beverages of different cultures were summarized.